2012
DOI: 10.1002/jat.2769
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the antifolate drug Methotrexate on the development of murine neural tube defects and genomic instability

Abstract: Impaired folate metabolism is considered a risk factor for neural tube defects (NTDs). However, the relationship between folate deficiency and the risk of NTDs remains unclear, because experimentally induced dietary folate deficiency is insufficient to cause NTDs in non-mutant mice. Methotrexate (MTX) is a specific folate antagonist that competitively inhibits dihydrofolate reductase (DHFR) activity. The objective of this study was to develop a folate dysmetabolism murine model, and study the development of NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
5
20
0
Order By: Relevance
“…We show that DHFR deficiency specifically during early head and facial development causes a narrower midface and malformed mouth shape, due to loss of jaw muscle and cartilage elements. This is consistent with reported effects in mammals where folate deficiencies or mutations to major pathway components can also result in craniofacial defects and smaller head size (Burgoon et al, 2002; Momb et al, 2013; Tang et al, 2005; Wang et al, 2014; Zhao et al, 2013). Further, DHFR mutations are associated with cleft lip in humans (Martinelli et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We show that DHFR deficiency specifically during early head and facial development causes a narrower midface and malformed mouth shape, due to loss of jaw muscle and cartilage elements. This is consistent with reported effects in mammals where folate deficiencies or mutations to major pathway components can also result in craniofacial defects and smaller head size (Burgoon et al, 2002; Momb et al, 2013; Tang et al, 2005; Wang et al, 2014; Zhao et al, 2013). Further, DHFR mutations are associated with cleft lip in humans (Martinelli et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we demonstrated that DHFR inhibition induced apoptosis is in part due to increased DNA damage. This was not a surprise, since cells with defective folate metabolism would fail to generate sufficient thymidine, which can lead to genomic instability and DNA damage (Andersen et al, 2005; Gu et al, 2002; Novakovic et al, 2006; Zhao et al, 2013). Additionally, oxidative stress generated when the folate pathway is abrogated can cause DNA damage-induced cell death (Bagnyukova et al, 2008; Ho et al, 2003; Kao et al, 2014; Rogers et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al . confirmed folate and folate‐related dysmetabolisms and found significant copy number variations in the NTD mice model induced by MTX (Zhao et al ., ). In the present study, we noticed that MTX also increases apoptosis and decreases proliferation, which may be a critical mechanism in NTDs induced by folate deficiency.…”
Section: Introductionmentioning
confidence: 97%
“…To determine the role of DHFR in oligodendrogenesis, we used a pharmacological inhibitor methotrexate (MTX) to inhibit DHFR in vivo . Different doses of MTX (2 mg/kg or 4 mg/kg) were intraperitoneally injected into pregnant mice and pups at E8.5, E15.5, P0 or P7, and the spinal cord or brain at different ages of pups were collected and analyzed 36 . MTX injection resulted in a dose-dependent downregulation of the DHFR mRNA level in the spinal cord and the folate level in serum (Fig.…”
Section: Resultsmentioning
confidence: 99%